THE DETERMINING FACTORS OF THE COMPETITIVE ADVANTAGE AND BUSINESS PERFORMANCE IN THE COASTAL COMMUNITIES IN NORTH MINAHASA REGENCY - Lisbeth Mananeke (Journal of Economics, Business, and Accountancy Ventura, 2012)
Competitive advantage and business performance can be considered potential factors in anybusinesses including in the coastal communities. This research analyses the effect of learningorientation on competitive advantage, the effect of learning orientation on performance, andthe effect of organization culture competitive advantage the businesses in North Minahasa,North Sulawesi. Primary data were taken from the owners of fishery business in coastal societywith the total number of 200 respondents with purposive sampling. The data were analyzedusing Structural Equation Model (SEM). It shows that intellectual capital has effect oncompetitive advantage. Yet, organization culture has no effect on competitive advantage. Theresearch also shows that learning orientation, intellectual capital, and competitive advantagehave effect on organization performance. On the contrary, organization culture and innovationhas no effect on organization performance.